2013
DOI: 10.1016/j.bbmt.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Th17-Associated Cytokines in Human Acute Graft-versus-Host Disease

Abstract: The role of Th17 cells and Th17-associated cytokines in the development of acute graft-versus-host disease (aGVHD) in clinical allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients is not well established. In the current study, a cohort of 69 allo-HSCT patients was examined for the percentages of Th17 and FoxP3(+) Treg cells and the expressions of RORγt and FoxP3 in peripheral blood mononuclear cells (PBMCs). The Th17 percentage and RORγt expression were significantly higher, whereas Treg p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…[1][2][3][4]38,39 In nontransplant settings, Th17 have in turn been described as protective in response to fungal infections and other pathogens, 40 pathogenic in multiple human autoimmune diseases, 41 and regulatory during inflammation resolution. 13 This heterogeneity in Th17 function has been attributed to their high degree of plasticity such that Th17 have been reported to transdifferentiate between these functional roles.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]38,39 In nontransplant settings, Th17 have in turn been described as protective in response to fungal infections and other pathogens, 40 pathogenic in multiple human autoimmune diseases, 41 and regulatory during inflammation resolution. 13 This heterogeneity in Th17 function has been attributed to their high degree of plasticity such that Th17 have been reported to transdifferentiate between these functional roles.…”
Section: Discussionmentioning
confidence: 99%
“…Whether these cells are also involved in the pathophysiology of alloimmune inflammation in aGVHD has remained an open question. In fact, although a growing amount of data support a role of Th17 cells in aGVHD in preclinical mouse models [6][7][8][9][10][11], studies in humans have reported conflicting results, suggesting [12][13][14][15] or dismissing [16][17][18] their involvement.…”
Section: Introductionmentioning
confidence: 99%
“…1,7 The role of T helper (Th)1-induced cytotoxic T lymphocytes as effector cells of aGVHD has been challenged by numerous mouse studies demonstrating an involvement of not only Th1 [7][8][9][10][11][12] but also Th2 8,9,12,13 and Th17 cells. 8,11,14,15 Studies in aGVHD patients investigating either circulating 12,[16][17][18][19][20][21] or skin-localized [17][18][19]22 T-cell subsets have yielded conflicting results. In aGVHD skin, either increased 17,22 or decreased numbers 18,19 of Th17 cells were reported to occur.…”
Section: Introductionmentioning
confidence: 99%